PENGGUNAAN BAP DAN NAA TERHADAP PERTUMBUHAN EKSPLAN BUAH NAGA (Hylocereus costaricensis) SECARA IN-VITRO - Suparaini Suparaini; Maizar Maizar; Fathurrahman Fathurrahman (UIR Press, 2013)
This research was conducted to examine the effect of BAP and NAA interactionally and individually on explant growth of dragon fruit in-vitro. The research was carried out at the Biotechnology Laboratory Faculty of Agriculture Riau Islamic University Pekanbaru. The experiment used the completely randomized design with two factors. The first factor was BAP concentration (B) with four treatments: B0 (0 ppm), B1 (2 ppm), B2 (4 ppm), and B3 (6 ppm). The second factor was NAA concentration (N) with four treatments: N0 (0 ppm), N1 (0.5 ppm), N2 (1.0 ppm), and N3 (1.5 ppm), so it was obtained 16 combination and 3 treatments. The observed parameter included age of shoot emergence, shoot number, and shoot height. As a result, the interaction use BAP ad NAA had effect on age of shoot emergence with BAP concentration of 4 ppm and 1,0 ppm. By using BAP only affected on the age of shoot emergence, percentage of explant life, and shoot height with BAP concentration of 4 ppm. Furthermore, the using NAA only had an effect on age of shoot emergence, shoot number and shoot height with concentration of 1.0ppm.